2016
DOI: 10.1007/s10295-016-1735-9
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for improving epothilone B yield in Sorangium cellulosum by the introduction of vgb epoF genes

Abstract: Epothilone B has drawn great attention due to its much stronger anticancer activity and weaker side effects compared with taxol. The relative low yield of epothilone B limited its application. In this study, we report the successful introduction of the vgb gene and the epoF gene into Sorangium cellulosum So ce M4 by electroporation for the first time, which was demonstrated by Southern blot analysis. Results of qRT-PCR, SDS-PAGE and western blot analysis confirmed the transcription and expression of the vgb an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…B. choshinensis is a Gram-positive bacterium that secretes proteins directly into culture, has low extracellular protease activity, produces no endotoxins, and is nonpathogenic. [16][17][18] It is an attractive protein expression host, but it has never been used as a production host for small recombinant bsAbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. choshinensis is a Gram-positive bacterium that secretes proteins directly into culture, has low extracellular protease activity, produces no endotoxins, and is nonpathogenic. [16][17][18] It is an attractive protein expression host, but it has never been used as a production host for small recombinant bsAbs.…”
Section: Discussionmentioning
confidence: 99%
“…16 This nonpathogenic Grampositive bacterium can secrete recombinant proteins in culture directly without concern for contaminating endotoxins, facilitating the purification process. 17,18 B. choshinensis has been used as a host for the production of industrial proteins as well as for biological products. Production of human epidermal growth factor (EGF) was reported in reclassified strain B. choshinensis HPD31; 19 however, there have been no reports of the production of bsAbs using this microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…Epothilones are potential anticancer agents by their greater water solubility and efficacy against paclitaxel-resistant tumors [13, 14]. Researchers tried many methods to improve the epothilones yield, including co-cultivation of different strains [15], mutation and high-throughput screening of high-producing strains [16], immobilization of strains [17], heterologous expressions [1824] and manipulation of related genes [25, 26]. However, the yield is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different approaches have been adopted to improve epothilone production. However, the difficulty in the genetic manipulation of S. cellulosum, the unclear genetic information for each S. cellulosum strain, and the lack of recognition for epothilone biosynthesis promoter and regulatory proteins impedes the progress of epothilone yield improvement in S. cellulosum (Ye et al, 2016). The 440-bp upstream sequence of the epothilone biosynthetic gene cluster from different S. cellulosum strains was cloned and identified, and the results indicated that the sequences of different promoters showed high similarity, whereas the transcriptional activities of these promoters remarkably vary probably because of the presence of stem-loop structures in the promoter sequences (Zhu et al,FIGURE 7 | The EMSA assay of native regulatory protein P3Fis and recombinant TALE-VP64 protein using biotin labeled core sequences of P3 promoter as probe.…”
Section: Discussionmentioning
confidence: 99%
“…However, epothilone yield remains low because of the difficulty in genetically manipulating S. cellulosum and the cytotoxicity of epothilones during the heterologous expression of epothilone biosynthesis cluster. The low yield of epothilones has limited their application in cancer treatment, and methods for enhancing epothilone yield and optimizing cultivation conditions are limited and random (Ye et al, 2016). Epothilone biosynthesis genes have been successively expressed in some bacteria, including Myxococcus xanthus and Burkholderiales sp.…”
Section: Introductionmentioning
confidence: 99%